The Analysis of Technology Acceptance Model (TAM) on Culinary MSMEs Marketplace in Garut Regency - Hamdani, Nizar Alam; Muladi, Rio; Maulani, Galih Abdul Fatah (Universitas Mercu Buana, 2024)
Objectives: The Objectives of this research are to examine the influence of perceived ease of use on perceived usefulness, the influence of perceived ease of use and perceived usefulness on behavioral intentions, the influence of behavioral intentions on usage behavior, the influence of subjective norms, and output quality. Demonstration Results of Perceptions of Usefulness and the Influence of Perceptions of Enjoyment on the Ease of Use of GoFood Marketplace among Culinary MSME Entrepreneurs in Garut Regency.Methodology: This research uses a quantitative approach and a survey method, which involves distributing a questionnaire to GoFood partner MSMEs in the Garut Regency. The collected data will then be analyzed using AMOS 27 software. The study focuses on Culinary MSMEs partnered with GoFood, or